International Islamic University Malaysia (IIUM) lecturers' use of social network sites (SNSs) for teaching : students' perception and its influence on their satisfaction - Landani, Zahra Mardani (Kulliyyah of Education, International Islamic University Malaysia, 2014)
This study aimed to investigate the extent to which International Islamic University Malaysia (IIUM) lecturers use SNSs in teaching and learning as perceived by students. It also examined the practices among IIUM lecturers in communication, assessment and sharing resources in using SNSs for their students. Further, this study examined the influence of teaching strategies (communication, assessment, sharing resources) by IIUM lecturers via SNSs on students' satisfaction. A total of 300 undergraduate and postgraduate students were selected from Kulliyyah of Information and Communication Technology (KICT) and Kulliyyah of Education (KOED) in IIUM. These students were purposively selected based on the usage of SNSs in teaching and learning process. A mix method research was used focusing on quantitative while qualitative research via interviews were carried out to enhance the findings. A self-constructed questionnaire with 23 items was used to measure (i) the frequency usage of SNSs in teaching and learning (Everyday to Never), (ii) teaching strategies and students' satisfaction (Strongly agree to Strongly disagree) on a 5- point Likert scale. A semi-structured interviews carried out among three students (2 from KICT and 1 from KOED). The items were first content validated by four experts and underwent pilot-testing before distributing to respondents. Based on the research questions, descriptive statistics, comparison of means and multiple regression analysis were used to analyse the data. The results show that the lecturers specifically include the social communication (54%) as the highest frequency use in teaching and learning activity. It is followed by updating information about the course twice a week (52%) and only 43% for sending learning resources. These results are further confirmed by the interviewees when they agree on the trend of SNSs use in teaching and learning. The level of agreement among the students in communication, assessment and sharing resources reveal above 50% (ranging 54% to 70%) indicating the actual practices of the lecturers in the teaching strategies. Finally, the overall result shows that the teaching strategies (communication, assessment and sharing resources) via SNSs significantly influence on students' satisfaction. The implications of the study show that teaching via SNSs will engage students in learning and facilitate the teaching process.